Endovascular treatment of primary mycotic aortic aneurysms: a 7-year single-center experience. Issue 9 (September 2018) - Luo, Yudong; Zhu, Jiechang; Dai, Xiangchen; Fan, Hailun; Feng, Zhou; Zhang, Yiwei; Hu, Fanguo
Objective: This study was performed to assess the efficacy and outcome of endovascular aneurysm repair (EVAR) for treatment of primary mycotic aortic aneurysms (PMAAs). Methods: Fourteen consecutive patients who presented with PMAA from April 2010 to July 2017 were retrospectively reviewed. Preoperative, intraoperative, and postoperative clinical data were recorded, and late infection-related complications and long-term survival were assessed. Results: The aneurysms were located in the abdominal aorta in 10 patients and in the left common iliac artery in 4 patients. Positive microbial cultures were found in 12 patients, including Salmonella species in 11 and Streptococcus in 1. The remaining two patients had negative culture results. Ten patients received preoperative antibiotics before elective EVAR for 7 ± 9 days after admission. Four patients who underwent emergent EVAR due to ruptured aneurysms were given their first dose of antibiotics before EVAR. Three patients underwent surgical drainage, and six underwent percutaneous drainage within 30 days after EVAR. No death occurred within 30 days of the initial procedure. The mean follow-up was 34.8 (range, 3–84 months). One patient underwent re-intervention to resolve obstruction of the iliac/femoral artery 5 months postoperatively. Relapse of infection occurred in six patients (42.8%) during follow-up; infection-related death occurred in three of these patients. The other patients recovered with either conversion to open radical surgery or medical therapy. The actuarial 7-year survival after EVAR was 75.7%. Conclusions: EVAR and aggressive antibiotic therapy might be suitable for PMAAs. Favorable results may be typical for infection caused by Salmonella .